Comparison of mobile application-based teledentistry method with face-to-face oral examination assessment - Burçin Avcı; Arife Kaptan (Arbu Academic Publishing, 2023)
Aim: The study aims to determine whether the mobile application-based teledentistry method is reliable in diagnosing and treating the intraoral findings of children aged 4 to 15 years by comparing intraoral examination and screening findings of the face-to-face and mobile application-based teledentistry. Methods: 115 patients were examined. Two pediatric dentists performed a face-to-face intraoral examination of the patients. Clinical examinations were accepted as the gold standard. Two extraoral and five intraoral images were obtained from the patients. The patient's information and the photos taken were transferred to the 'TeleDiş' mobile application developed specifically for the research. Six remote pediatric dental specialists, identified as teledentists, conducted their examinations using photos of the patients obtained through the "TeleDiş" mobile app. The WHO oral health evaluation form for children was adapted and used to record the findings of the patients. When the compatibility between the clinical examination dentists and the teledentistry group in terms of categorical variables, Cohen's Kappa Statistics was used to examine the compatibility between two physicians, and Fleiss' Kappa Statistics was used while examining the compatibility between three or more physicians. Results: According to the findings of the study, a statistically significant and very good agreement was obtained between the clinician (gold standard) and teleconsultant physicians in terms of dental examination (p<0.001). Specificity results were found to be higher than sensitivity in dental examination parameters. Although the sensitivity is above 80% and the specificity is consistently above 90%, the current model has a higher probability of giving false positive results than false negative results. Conclusions: Our study demonstrated that the combination of the store-and-forward method at the mobile application level and the use of a smartphone camera provides a valid and reliable remote scanning method for evaluating intraoral results, despite its current limitations.